Cost-effectiveness of anticoagulation in patients with nonvalvular atrial fibrillation with edoxaban compared to warfarin in Germany - Krejczy, Martin; Harenberg, Job; Wehling, Martin; Obermann, Konrad (BioMed research international, 2015)
We compared the cost-utility analysis for edoxaban at both doses with that of dabigatran at both doses, rivaroxaban, and apixaban (non vitamin K antagonist oral anticoagulants, NOAC) in a German population. Data of clinical outcome events were taken from edoxaban’s ENGAGE-AF, dabigatran’s RE-LY, rivaroxaban’s ROCKET, and apixaban’s ARISTOTLE trials. The base-case analyses of a 65-year-old person with a CHADS2 score >1 gained 0.17 and 0.21 quality-adjusted life years over warfarin for 30 mg od and 60 mg od edoxaban, respectively. The incremental cost-effectiveness ratio was 50.000 and 68.000 euro per quality-adjusted life years for the higher and lower dose of edoxaban (Monte Carlo simulation). These findings were also similar to those for apixaban and more cost-effective than the other NOAC regimens. The current market costs for direct oral anticoagulants are high in relation to the quality of life gained from a German public health care insurance perspective. The willingness-to-pay threshold was lowest for 60 mg edoxaban compared to all direct oral anticoagulants and for 30 mg edoxaban compared to dabigatran and rivaroxaban.